Augustyn i Jan Kasjan o dopuszczalności kłamstwa, które jest bezwzględnym grzechem - Nehring, Przemysław (Collectanea Philologica, 2023)
The author of the article analyzes the similarities and diﬀerences in Augustine’s and John Cassian’s approaches to both the nature of lying as a sin and its possible permissibility or at least its pardonability in strictly deﬁned situations. He argues for the position that it is impossible to say unequivocally whether Cassian undertook a conscious polemic with the Bishop of Hippo on this issue or even whether he was at all familiar with both or any of his treatises on lying. The fundamental diﬀerence between them regarding the issue of accepting intentionality in committing this absolute sin stems from the nature of the writings in which they articulated their views, their rhetorical context and the anthropological perspective of both authors.